PERBANDINGAN PORTABILITY, REUSABILITY, DAN INTEROPERABILITY PADA E-COMMERCE BERBASIS OPEN SOURCE - Irfan, Rifqi Imaduddin; Nugraha, Aji Saka; Anggrainingsih, Rini (Jurnal Sistem Komputer, 2018)
This paper will focus on comparison of portability, reusability, and interoperability values on open source-based e-commerce. The aim of comparing these three values is to find out which e-commerce has the best portability, reusability, and interoperability values. E-commerce software that will be tested are Magento 2.0, OpenCart 2.3.0.2, and WooCommerce 3.07. It has been chosen because this software are included in â€œThe Top 10 Open Source e-Commerce Platformsâ€ by CMS Critic website. Portability and reusability assessment is based on modularity, self-descriptive, and simplicity subfactor. The result obtained which e-commerce has the best value of the three factors tested is OpenCart with the best scores in the factor of portability and interoperability.